STUDENT’S PERCEPTION OF PROJECT-BASED LEARNING MODEL WITH CANVA IN ENGLISH WRITING CLASS AT SMK NEGERI 1 BUSUNGBIU - Desak Made Indah Dewanti (UHN IGB Sugriwa Denpasar, 2023)
The popularity of Project-Based Learning (PBL) is increasing as it focuses on students’ learning process than the teaching process. There are ample sources showing that using PBL can enhance students' skills, abilities, and interests. However, in the context of Vocational High School students in Indonesia, there is still a limited amount of research on perceptions of PBL, especially when it is combined with the use of media, for example, Canva Application. The aim of this study was to assess students' attitudes toward the Project-Based Learning (PBL) model and the utilization of the Canva application in an English class. The research employed questionnaires and interviews as data collection techniques. The research participants were 29 students from the XI Hospitality class at SMK Negeri 1 Busungbiu. The findings obtained through the questionnaires and interviews indicated that the students exhibited favorable perceptions of the PBL model. The materials used in the PBL approach were perceived to be clear, captivating, and easily accessible, and was observed to bolster students' motivation and writing skills. Moreover, the employment of the Canva application for writing in English was also well-received by the students, despite the identification of certain limitations associated with the application.